MEMBANGUN INTERAKSI POSITIF DAN RESPONSIF PADA PEMERINTAH DESA LIWULAGAN MELALUI MEDIA BERUPA PAPAN INFORMASI DAN KOTAK SARAN - Dulin, Gabriel Lagi; Sahan, Meylisa Yuliastuti; H. Molan, Kristianus Simon (LPPM IAI Muhammadiyah Bima, 2025)
The village government has an important role in realizing transparent, accountable, and participatory governance. One effort that can be made is to build positive and responsive interactions between the village government and the community. This study aims to describe how information boards and suggestion boxes can be used to strengthen two-way communication between the Liwulagan Village government and its residents. Information boards are used as a means of conveying information about village programs, activity agendas, and accountability reports, while suggestion boxes are a medium for the community to convey aspirations, criticisms, and suggestions directly. The implementation of activities is carried out through field practice, where the team together with the village government installs information boards and places suggestion boxes in strategic locations in the village. The results of observations show that this media is able to increase community participation and encourage the village government to respond more quickly to the needs of residents. However, challenges such as lack of community awareness in providing input and limited resources still need to be overcome. Overall, the use of information boards and suggestion boxes has proven effective in building positive communication and strengthening relations between the village government and the community in Liwulagan Village. Keywords: Interaction, Village Government, Information Boards, Suggestion Boxes, Community Participation.